Faktor Lingkungan dan Perilaku yang Berpengaruh terhadap Kejadian Filariasis di Daerah Endemis Kota Pekalongan - Yusuf Lensa Hamdan; Suharyo Hadisaputro; Ari Suwondo; Muchlis AU Sofro; Mateus Sakundarno Adi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2019)
Background: Filariasis is a disease still become a health problem in Indonesia. South Pekalongan District is one of the endemic areas of filariasis. Filariasis is influenced by several factors such as environmental factors, socio economic and community behavior. The objective of this study was to determine the influence of environmental factors, socio economic factor and behavior that contributed to the incidence of filariasis cases in South Pekalongan District.Methods: This research was an observational research with a case-control approach. Case in this study was filariasis cases and for control was people suffer from filariasis. The number of each case and control is 40. Data was taken by observation and interview. Data collected was analyzed by using logistics regression.Results: Multivariate analysis shows that out of 11 (eleven) variables there is 1 variable which is proven to influence the incidence of filariasis in South Pekalongan District in July 2018, it was use of anti-mosquito drugs (OR = 29,231, CI 95% = 5,998 – 142,445).Conclusion: Not using mosquito repellent is the most dominant risk factor for the occurrence of filariasis transmission. People are advised to use mosquito repellent while sleeping or during activities at night. It is necessary to perform health promotion and extend the information related to filariasis in order to improve community knowledge.